A clinical investigation of extracranial metastases in 17 cases of intracranial solitary fibrous tumors - Chao Wang; Jiang Li; Gang Li; Da-Yun Feng; Ying-Xi Wu; Jun-Ting Li; Di Yang; Jia-Hua Zhou (World Journal of Surgical Oncology)
Abstract Objective This study aimed to evaluate the clinical features, pathological progression, and treatment strategies for distant metastases of intracranial solitary fibrous tumors (ISFTs). Methods A retrospective analysis was conducted on 17 patients with ISFTs and documented distant metastases, treated at a single institution between 2001 and 2023. Disease progression and treatment outcomes were systematically reviewed. Results Of the 17 patients, 14 experienced in situ recurrence following resection of the primary intracranial tumor, necessitating a total of 41 intracranial lesion resections. Based on initial pathological assessments, the cases were classified as grade 1 (n = 4), grade 2 (n = 10), and grade 3 (n = 3) ISFTs. Over time, all but one grade 1 and grade 2 tumor were reclassified as grade 3. Following initial resections, 13 patients underwent local radiotherapy and 2 received systemic chemotherapy prior to the development of distant metastases. After metastasis, 8 patients underwent metastatic tumor resection, while 7 received conservative treatment, and 2 did not undergo any intervention. A total of 10 patients, including 2 who withdraw treatment, were followed until the end point. The average survival time for this group was 106 months (range: 23–190 months), with an average survival of 20.89 months (range: 2–60 months) following the diagnosis of distant metastases. Mortality was attributed to functional failure of vital organs, tumor burden, systemic failure, or cachexia. The remaining 7 cases underwent active treatment and are still being monitored. The average total follow-up duration was 145.57 months (range: 95–256 months), while the average follow-up time after distant metastasis diagnosis was 33.42 months (range: 13–72 months). Conclusion Surgical resection remains the primary treatment modality for ISFTs, with adjuvant radiotherapy recommended to delay recurrence. Recurrent tumors frequently exhibit pathological grade progression. Gamma knife radiosurgery is effective for small recurrences, while larger tumors often require repeated surgical resections to manage the primary lesion. The development of distant metastases signifies advanced disease, requiring a multidisciplinary approach that incorporates surgical resection, radiotherapy, and targeted therapies. Distant metastasis remains the primary cause of mortality following active treatment.